Analysis of Consumer Preferences on Online Delivery Plastic Packaging Consumption Behavior: An Indonesian Survey - Ira Rumiris Hutagalung; Indriyani Rachman (Universitas Diponegoro, 2023)
A heavy dependency on online shopping platforms and home delivery, together with emerging post-pandemic responses from developing nations like India, China, Brazil, and primarily Indonesia, sum up a surge in demand for unsustainable plastic packaging techniques. Consumer preference as the center of successful commercial strategy and become a consideration in waste management studies. This study aims to develop an understanding of consumer preference factors as a response to tackling the plastic problem due to the online delivery system in Indonesia. Google's web-based platform is used to capture the number of online deliveries in a weekly period. A five-level Likert scale measures attitudes, social norms, or perceptions toward a constructed questionnaire. From the ordinal regression analysis, younger people intend to consume more with online platforms, and the more people don't have a proper waste collection, the higher they will consume online plastic delivery.